Penerapan Unsur Tindak Pidana oleh Penyidik Terhadap Tindakan Penebangan Pohon pada Kawasan Hutan Lindung - Pratama, Yuda Amgu; Ismansyah, Ismansyah (Universitas Ekasakti, 2023)
Reports of cases of illegal logging that occurred in areas of West Sumatra province were based on data from the Ditreskrimsus and Satwil Sejajaran Polda West Sumatra that reports of criminal acts of illegal logging at the Pasaman Police were 5 (five) cases, Dharmasraya Police were 2 (two) cases, Pesisir Selatan Police with 9 (nine) cases, Tanah Datar Police with 3 (three) cases. This study uses an empirical juridical approach. The Application of Elements of Crime by Investigators at the Tanah Datar Police Criminal Investigation Unit Against the Action of Logging Trees in Protected Forest Areas. Subjectively the element applied is